2014
DOI: 10.1016/j.apmr.2014.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of Age on Disability for Individuals With Spinal Cord Injuries

Abstract: Objective To examine the additive effect of age on disability for adults with SCI. Design Prospective cohort study. Setting Spinal Cord Injury Model Systems. Participants The study sample individuals with SCI with a discharge motor-FIM score and at least one follow-up motor-FIM score who also provided measures of other covariates (N=1,660). Seventy-nine percent of the sample was male, 72% was white, 16% had paraplegia, incomplete; 33.0% had paraplegia, complete; 30% had tetraplegia, incomplete; and 21% h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 19 publications
1
21
1
1
Order By: Relevance
“…Increased age at injury is associated with poorer functional outcomes 41, 42 and increases in comorbidities and secondary complications. 43 It has been reported that patients with a C1–C4 lesion spend 27% longer in acute care than patients with a C5–C8 lesion, and 77% longer than patients with paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Increased age at injury is associated with poorer functional outcomes 41, 42 and increases in comorbidities and secondary complications. 43 It has been reported that patients with a C1–C4 lesion spend 27% longer in acute care than patients with a C5–C8 lesion, and 77% longer than patients with paraplegia.…”
Section: Discussionmentioning
confidence: 99%
“…Despite advances in the last decades, people with disabilities still have worse health prospects, lower levels of schooling, lower economic participation, higher poverty rates, lower life expectations and worse quality of life. 6 As a consequence, people with disabilities are living longer, yet they face an accelerated aging process. 7 Even though aging of people with disabilities is admittedly a good reason to celebrate, its challenging character should also be recognized.…”
Section: Introductionmentioning
confidence: 99%
“…3 If referred to a specialized center, elderly people with SCI may gain a similar rate of functional improvement 7 ; but because older patients generally have lower functional scores at admission, they also show worse rehabilitation outcomes compared to people who are injured at a younger age. 4,[8][9][10] The life expectancy of the population with SCI has grown over the last 50 to 60 years. 11 Many people with a new SCI can expect to live another 30 to 40 years or more.…”
mentioning
confidence: 99%
“…However, the reverse -higher age at injury is an independent predictor of worse functional outcomes -has also been shown. 10 We therefore used data from earlier research with the following objectives: (a) to describe the levels of participation and life satisfaction in individuals with SCI aged 65 years or older, and (b) to analyze differences in participation and life satisfaction between individuals injured before 50 years of age or at or after 50 years of age.…”
mentioning
confidence: 99%